Cell Tropism and Pathogenesis of Measles Virus in Monkeys - Kato, Sei-ich; Nagata, Kyosuke; Takeuchi, Kaoru (Frontiers in Microbiology, 2012)
Measles virus (MV) is an enveloped negative strand RNA virus belonging to the family of Paramyxoviridae, genus Morbillivirus, and causes one of the most contagious diseases in humans. Experimentally infected non-human primates are used as animal models for studies of the pathogenesis of human measles. We established a reverse genetics system based on a highly pathogenic wild-type MV. Infection of monkeys with recombinant MV strains generated by reverse genetics enabled analysis of the molecular basis of MV pathogenesis. The essential in vivo function of accessory genes was indicated by infecting monkeys with recombinant MV strains deficient in the expression of accessory genes. Furthermore, recombinant wild-type MV strains expressing enhanced green fluorescent protein enabled visual tracking of MV-infected cells in vitro and in vivo. To date, three different molecules have been identified as receptors for MV. Signaling lymphocyte activation molecule (SLAM, also called CD150), expressed on immune cells, is a major receptor for MV. CD46, ubiquitously expressed in all nucleated cells in humans and monkeys, is a receptor for vaccine and laboratory-adapted strains of MV. The newly identified nectin-4 (also called poliovirus-receptor-like-4) is an epithelial cell receptor for MV. However, recent findings have indicated that CD46 acts as an MV receptor in vitro but not in vivo. The impact of the receptor usage of MV in vivo on the disease outcome is now under investigation.